Cybermisogyny: Hate Against Women and Gendertrolling Manifestation on Instagram - Muhammad Dicka Ma'arief Alyatalatthaf (FISIP Universitas Atma Jaya Yogyakarta, 2021)
Cybermisogyny is hateful behavior against women on social media. This study aims tofind the forms of cybermisogyny that occur on @viavallen’s Instagram. Descriptive qualitative usedwithin the framework of Teun A. van Dijk’s Critical Discourse Analysis (CDA) which focuses on textanalysis, social cognition, and social context. This research uses gendertrolling theory from Karla Mantilla. The results showed: (1) cybermisogyny that occurred on @viavallen’s Instagram was dominated by online abuse and sexual harassment; (2) message producers tend to be permissiveto harassment behaviors; (3) the dimensions of power and access are the main factors in theoccurrence of cybermisogyny.